Desafios e mudanças nas empresas de construção civil e as relações de trabalho - Maria Antónia R. F. Lopes (Cadernos de Estudos Africanos)
The contractors of the civil construction, in Mozambique,face great dependence on the strategical level, namely in the weight assumed by the State as customer, regulator and employer. The most frequent strategicalchoices assume trends that go from the defensive to the reactive in the management  of the work force. The contractors have showed the necessityof an increasedderegulation of the labor law, of flexibilization, which is leading to a diversification of forms associated to further precarization of the work. The lived situation is disastrous in the building sites and it corresponds neither to the speeches of the politicians nor to the philosophyof the working legislation. The absence of a continuous professional training assumes enormous relevance. Therefore, to articulate the liquidity of the companies with the systematic delays of the outlays (on the part of the state institutions) and the professional qualification of the technicians of the sector appears, thus, as the main challenge for the contractors and those responsible for training.